Fabrication and characterization of regenerated Antheraea pernyi silk fibroin scaffolds for Schwann cell culturing. (August 2019) - Zou, Shengzhi; Wang, Xinru; Fan, Suna; Zhang, Jiaming; Shao, Huili; Zhang, Yaopeng
Graphical abstract: Highlights: Antheraea pernyi silk scaffolds were prepared by lyophilization. RASF scaffold structure can be transformed between lamellar and porous structures. RASF scaffolds have excellent cytocompatibility with Schwann cells. Abstract: Antheraea pernyi silk, which is from a kind of non-mulberry silkworm produced in China, has better mechanical properties and cytocompatibility than the extensively studied silk from mulberry silkworm (Bombyx mori) . In this work, the regenerated Antheraea pernyi silk fibroin (RASF) scaffolds were prepared from RASF aqueous solutions with different concentrations by a freeze-drying method. The morphologies, structures and properties of the obtained RASF scaffolds were investigated. It was found that with the decrease of RASF solution concentration and the increase of freezing temperature, the porosity of the scaffold increased while its apparent density decreased. The micro-morphology of the scaffold from the 1 wt% RASF solution was irregular. When the solution concentration was increased to the range of 4–13 wt%, the micro-morphologies of the obtained scaffolds mainly showed lamellar-like structure. And with the increase of solution concentration, the lamellar gap of the scaffold decreased while the lamellar thickness of the scaffold increased. However, with the further increase of solution concentration, the morphology of scaffold could gradually transfer into porous structure. In addition, the scaffold micro-morphology could be also affected by freezing temperature. Moreover, with the increase of RASF solution concentration or (and) the decrease of freezing temperature, the obtained scaffold had higher content of β-sheet conformation and higher crystallinity, which could improve its mechanical properties. It was further found that the swelling ratio and degradation rate of RASF scaffold prepared for tissue engineering increased with the decrease of solution concentration. The results of MTT indicated that the obtained RASF scaffold had no cytotoxicity. Moreover, the results of field emission scanning electron microscopy and laser confocal scanning microscopy revealed that the viability, cytocompatibility and migration ability of Schwann cells cultured on RASF scaffold were much better than those cultured on regenerated Bombyx mori silk fibroin (RBSF) scaffold. The RASF scaffold prepared in this work may have great potential applications in the area of nerve tissue engineering.